TECHNOLOGY OF ENDOGENOUS GROWTH AS THE BASIS OF THE DETERMINANT DEVELOPMENT OF DOMESTIC INDUSTRIAL ENTERPRISES IN THE CONDITIONS OF DIGITALIZATION - SHEPELENKO, Svitlana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
In today's conditions, when the global economy is experiencing radical changes caused by digitalization, technological development and the need to adapt to new realities, the topic of endogenous growth is becoming especially relevant. Rapid changes in technology and the emergence of new digital platforms are changing the structure of the economy, requiring companies to be flexible, innovative and able to quickly respond to new challenges. In these conditions, models of endogenous growth, which focus on the use of internal resources such as human capital, innovation and technological progress, become the basis for the formation of a long-term development strategy. They make it possible to effectively use the opportunities provided by digitalization and ensure sustainable economic growth even in conditions of global uncertainty.The effectiveness of endogenous growth as the basis of determinant development has changed significantly today. The further development of domestic industrial enterprises, the success of reforms depends on the introduction of innovative technologies in all sectors of the economy. Over the last decade, one of the main directions of reform is the active introduction of modern digital technologies. They will make it possible to reach a new level of quality-of-service provision, maintenance and cost reduction, which will significantly affect the cost price and, accordingly, the price. These technologies will help domestic industrial enterprises to work successfully in today's tough competitive environment.The modern conditions of the development of industrial enterprises in Ukraine are characterized by dynamic changes caused by the rapid introduction of digital technologies. In the conditions of global digitalization, the importance of innovations, which become the basis for the endogenous growth of enterprises, is growing. This concept involves development through internal resources and capabilities, which allows enterprises to achieve decisive development and increase their competitiveness.Endogenous growth technology is based on internal factors, such as innovation, knowledge and human capital, which contribute to the stable and sustainable development of enterprises. In the conditions of digitization, this technology acquires special importance for domestic industrial enterprises. The introduction of new digital technologies, such as artificial intelligence, automation and data analytics, is critical for increasing the efficiency and competitiveness of domestic industrial enterprises. This provides an opportunity to reduce costs, optimize processes and introduce innovations. Digitization is an important element that strengthens the influence of endogenous factors. The use of digital technologies makes it possible to optimize production processes, reduce costs, improve the quality of products and services, and increase management flexibility.In the conditions of digitalization, the technology of endogenous growth becomes critically important for the successful development of domestic industrial enterprises. The use of internal resources and the potential of enterprises, the integration of the latest digital technologies and innovative approaches allows achieving high efficiency and decisive development, which in turn contributes to increasing competitiveness on the world market. The technology of endogenous growth in the conditions of digitalization is the key to the long-term and decisive development of domestic industrial enterprises. The integration of innovation, human capital development, effective knowledge management and the implementation of digital technologies ensure high productivity and competitiveness. The use of these approaches contributes to the creation of a dynamic economy capable of responding effectively to the challenges and opportunities of the digital age.
Keywords: digital technologies; enterprise; digital economy; endogenous growth theory; endogenous development; determinant development